2006
DOI: 10.1021/cm052811d
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Synthesis of Cobalt Nanoparticles

Abstract: Co nanoparticles with three different crystal structures were synthesized in a microfluidic reactor through manipulation of reaction times, flow rates, and quenching procedures. Cobalt nanoparticles of facecentered cubic (β) phase were obtained from a high flow rate of the reactants followed by in situ quenching of the reaction. hcp and -cobalt nanoparticles were obtained at a low flow rate of the reactants followed by in situ quenching and delayed quenching, respectively. The crystal structures were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(162 citation statements)
references
References 75 publications
5
153
0
2
Order By: Relevance
“…[36,48] . The 4 nm Co NPs with fcc, hcp and epsilon phases have blocking temperatures of -143 ° C, 1 ° C and 17 ° C, respectively [49] . After annealing, the coercivity of CoPt [50] , FePt [39,51] and FePd [35,50] NPs increases due to a transition from the disordered face-centered cubic (fcc) to ordered facecentered tetragonal (fct) structure.…”
Section: Biomedicalmentioning
confidence: 99%
“…[36,48] . The 4 nm Co NPs with fcc, hcp and epsilon phases have blocking temperatures of -143 ° C, 1 ° C and 17 ° C, respectively [49] . After annealing, the coercivity of CoPt [50] , FePt [39,51] and FePd [35,50] NPs increases due to a transition from the disordered face-centered cubic (fcc) to ordered facecentered tetragonal (fct) structure.…”
Section: Biomedicalmentioning
confidence: 99%
“…Co NPs can exist in either the hexagonal closed packed (HCP), face-centered cubic (FCC), body-centered cubic (BCC), or epsilon ϵ (similar to the β phase of Mn [13]) phases, the relative stability of which depends on the route of formation [17][18][19] host matrix [20][21][22] and thermal history [23,24]. Of these four phases, HCP has the highest coercive field [13,25] and is thus the most obvious candidate for ultrahigh-density recording applications. Co nanorods and nanowires also exhibit unique perpendicular magnetic anisotropy, coercivity, remanence, and activation volumes that are heavily dependent on the nanorod length (or equivalently, major diameter) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the anaerobic conditions, Cu nanoparticles are stable in the microfluidic environment. Another important application of microfluidic synthesis, the synthesis of nanoparticles with two or more crystalline phases, realized by Kumar et al is shown in the example below ( Figure 17) for cobalt nanoparticles [29]. Figure 17.…”
Section: Synthesis Of Inorganic Nanoparticlesmentioning
confidence: 99%